(untitled) (International Journal of Environmental Sciences, 2024)
Patient safety remains a critical priority in healthcare organizations, particularly in hospital environments where nurses play a central role in monitoring patients and ensuring safe clinical practices. Leadership behaviors have been increasingly recognized as important factors that influence safety culture, staff engagement, and healthcare quality. This study aims to examine the influence of idealized influence and inspirational motivation on patient safety outcomes among nurses at King Faisal Specialist Hospital in Riyadh, Saudi Arabia. A quantitative cross-sectional research design was employed to investigate the relationships between transformational leadership behaviors and patient safety outcomes. Data were collected from 109 nurses using a structured questionnaire measuring idealized influence, inspirational motivation, and patient safety outcomes. Statistical analyses included reliability testing, descriptive statistics, correlation analysis, and multiple regression analysis to examine the proposed relationships. The results indicate that both idealized influence and inspirational motivation have positive and significant effects on patient safety outcomes. Inspirational motivation demonstrated a stronger influence on patient safety outcomes compared with idealized influence, suggesting that motivational leadership behaviors may play a particularly important role in encouraging nurses to engage in safe clinical practices. The findings highlight the importance of leadership behaviors that foster trust, motivation, and professional commitment among nursing staff. Effective leadership can contribute to strengthening patient safety culture and improving healthcare quality within hospital environments. The study provides valuable insights for healthcare administrators and policymakers seeking to enhance patient safety through leadership development initiatives. Strengthening transformational leadership competencies among nurse leaders may therefore represent an effective strategy for improving patient safety outcomes in healthcare organizations.